Patrimonialismo, Democracia direta e Neopopulismo na América Latina - Rodríguez, Ricardo Vélez (Diálogos Latinoamericanos, 2011)
The phenomenon of populism is expanding, not only in Latin America but also around the rest of the world. The uncertainties generated by the globalization of the labor market in developed countries, including the market economy of nations until recently dependent on totalitarian regimes (as in Eastern Europe); the wave of democratic regimes in Latin America emerged in the last twenty years and they failed to respond satisfactorily to the challenges of developing their societies; the liberal reforms introduced in the economies of sub-developed countries over the past decades, in the light of the "Washington Consensus" (reforms which, although reduced inflation in general, does not have the expected results of the field of productivity) still suffocated by nationalism and traditions of familiarity in the management of public affairs; the democratization sui generis (with a strong presence of traditional and charismatic leadership), in countries of the Islamic World (Syria, Libya, Iran); the entry of African nations in the postcolonial period (during the second half of last century) in the way of regularization of democratic life (in a way still strongly marked by tribalism), the deceleration of the U.S. economy and the brakes that this phenomenon is producing in other economies, particularly on the American continent; these are some of the variables that have contributed to the rise of populism, which may be considered as a kind of disease that affects the democracies in a time of crisis. Such wide phenomena deserve to be studied in detail. This text will not focus on the characterization of Populism in its various manifestations throughout the twentieth century. The focus will be on the phenomenon of the neo-populism that normally occurs in society today. It is, therefore, a current phenomenon that is limited to the last two decades of the previous century and it includes, of course, the first years of the 21st century. I intend in this article, to develop two aspects: I) the concept of neo-populism II) how this phenomenon affects the democratic life of South America, today and in the near future